2014
DOI: 10.1097/sle.0000000000000009
|View full text |Cite
|
Sign up to set email alerts
|

Ligasure Versus Stapled Hemorrhoidectomy in the Treatment of Hemorrhoids

Abstract: The aim of this meta-analysis was to compare the outcomes of Ligasure hemorrhoidectomy and stapled hemorrhoidectomy for prolapsed hemorrhoids. Original studies in any language were searched from MEDLINE database, PubMed, Web of science and the Cochrane Library database, and Wangfang database. Randomized control trials that compared Ligasure hemorrhoidectomy with stapled hemorrhoidectomy were identified. Data were extracted independently for each study, and a meta-analysis was performed using fixed and random-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 9 publications
0
22
0
2
Order By: Relevance
“…Moreover, the incidence of residual skin tags and prolapse was significantly lower in the LigaSure group than in the SH group. The data also indicated that the incidence of recurrence was significantly lower in the LigaSure group than in the SH group [62,63].…”
Section: Resultsmentioning
confidence: 48%
See 1 more Smart Citation
“…Moreover, the incidence of residual skin tags and prolapse was significantly lower in the LigaSure group than in the SH group. The data also indicated that the incidence of recurrence was significantly lower in the LigaSure group than in the SH group [62,63].…”
Section: Resultsmentioning
confidence: 48%
“…Some meta-analyses when looking at long-term outcomes after SH and conventional hemorrhoidectomy found higher recurrence rates following SH [61][62][63].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies on short-term outcomes have demonstrated that when compared to conventional hemorrhoidectomy, SH is quicker to perform and patients experience less postoperative pain, postoperative bleeding, wound complications, and constipation [96][97][98][99][100][101]. Hospital stay and time to return to normal activities were also shorter.…”
Section: Sh Is An Effective Technique For the Treatment Of Hd When Cmentioning
confidence: 99%
“…The LigaSure ™ Vessel Sealing System (LVSS) is commonly used for tissue preparation due to its safe and reliable coagulation of tissue resulting in reduced blood loss and has been successfully tested for hepatic, esophageal, and proctologic surgery in recent years [10][11][12][13]. Due to its properties regarding reliable tissue coagulation and sealing, the LVSS may have benefits such as a high reproducibility as well as a fast method to seal the bowel endings for creation of intestinal anastomoses compared to the thus far widely used standard methods.…”
Section: Introductionmentioning
confidence: 99%